Conflicts and negotiation processes in the course of power grid extension in Germany. (19th May 2018) - Kühne, Olaf; Weber, Florian
Abstract: The political decision to decommission all German nuclear power plants by 2022 has brought significant changes in the areas of energy supply and transmission. The development of renewable energies has become the centrepiece of political activity, and the reorganisation and extension of the existing power grid is widely considered a necessary consequence. However, this logic is not espoused by all. Some reject the need for grid extension altogether; others criticise the construction of overhead power lines and favour buried cabling. The issue has sparked massive citizens' protests in which specific arguments recur with regularity, notably 'disfigurement of the landscape', 'destruction of nature' and—in Bavaria—'loss of home environment'. The article examines the central lines of argumentation used both in favour of and against grid extension from a discourse theory perspective, with a focus on 'landscape' and 'home'. This entails a social-constructivist understanding of landscape.